Information security awareness amongst students in IIUM - Ahmed, Ibrahim Nasreldin Ibrahim (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
Information security awareness (ISA) simply implies a focus on security to protect information. When implemented in an educational setting, such as the International Islamic University Malaysia (IIUM), its purpose is then to educate the university community about the potential risks that could arise if lack of attention towards ISA is not highlighted. By understanding risks and having the proper behavior when it comes to Information Security (InfoSec), it may be possible to avoid any undesirable outcomes. The purpose of this research therefore is to study the awareness of ISA amongst students in IIUM. To this end, data collection was conducted through the administration of 300 questionnaires using a quantitative approach. Data analysis was performed by putting the questionnaires through SPSS. The findings show that the participants of this study are well-adapted with information on security issues and possess a high degree of awareness. The results also indicate that most of the participants are aware of the importance of using a strong password, conducting a regular backup of their data, not being tempted to download from unknown sources, and are aware of the potential risks that could occur if their computers are infected by malware. Moreover, the findings also indicate that information security risk, internet skill and the gender of respondents have a unique statistically significant variance to information security awareness level amongst the students.